2006
DOI: 10.1590/s1807-59322006000300006
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Dynamometry in Elderly Women Undergoing Total Knee Arthroplasty: A Comparative Study

Abstract: Aquino M de A, Garcez-Leme LE. Isokinetic dynamometry in elderly women undergoing total knee arthroplasty: a comparative study. Clinics. 2006;61(3):215-22. OBJECTIVE:The present study assessed the reliability and validity of isokinetic dynamometry in the qualitative determination of the evolution of total knee arthroplasty. Cases: 20 patients whose mean age was 71.35 years, undergoing knee arthroplasty, and 25 controls whose mean age was 71.36 years. METHOD: Computerized isokinetic assessment of flexor and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…It has been recently used to analyze the evolution of total knee arthroplasty of elderly patients. 24 The H/Q ratio shows the equilibrium condition among the forces which act on the knee. There is evidence that a H/Q ratio below 60% is related to ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently used to analyze the evolution of total knee arthroplasty of elderly patients. 24 The H/Q ratio shows the equilibrium condition among the forces which act on the knee. There is evidence that a H/Q ratio below 60% is related to ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…A dinamometria isocinética é um dos métodos mais acurados para avaliação muscular, oferecendo informações sobre a dinâmica e desempenho dos músculos testados 24 . As mensurações são feitas por um dinamômetro computadorizado que permite arcos de movimento em uma velocidade angular constante pré-determinada 25 .…”
Section: Introductionunclassified
“…12 Patients' age was limited, because comparing patients older than 75 years and younger than 55 years could show a significant strength difference due to age. 13,14 In the study by Tria and Coon 15 patients' age ranged from 51 to 84 years (mean: 67 years), and, in the study by Berger et al 12 age ranged from 50 to 79 years (mean: 68 years). In our study, a difference was found in the mean values for age, but the statistical analysis showed no correlation between isokinetic dynamometry parameters and age.…”
Section: Discussionmentioning
confidence: 96%
“…As we studied aged women not practicing sports and with knee osteoarthrosis, we chose not to assess dominant and non-dominant sides. 13,14 The kind of anesthesia and pain relief was standardized in order to enable patients to start rehabilitation protocol with the same status.…”
Section: Discussionmentioning
confidence: 99%